(untitled) (The Journal of Psychology and Sociology, 2017)
This paper studies the psychological, intellectual, behavioral features of orphans and children who are brought up in families. In connection with the research for this purpose we have been analyzed and identified root causes of problems in children. It describes the behavioral characteristics of children, furnished in the family, is written on the adaptation to the peculiarities of the new family of girls and boys. As a result of consideration of scientific research, the intellectual development of girls increased significantly after foster care adoption. We consider the symptoms, especially the development of «institutional au- tism» in children-orphans, reveals the fact that in the case of provision of family education. The authors describe the transformation of the emotional, psychological, behavioral, physiological state of orphans after the transfer to the family education. Аdaptation processofmany children fromorphanage is dangerous. They are not able to build elations exhibit bad behavior and self-assured. Their addiction to adult takes more aggressive than their peers. As closed institution havenot connection with outside world, and children of- ten change their home caregivers, they get used to the instability and left unat- tended. Daily activity of childregulated by the schedule, they do not have the right to choose toys and other things. So unfocused action leads to the fact that a child can not live on their own and can not independently make a decision.